Prarancangan Pabrik Biodiesel Dari Crude Palm Oil dan Metanol Dengan Proses Transesterifikasi Kapasitas 140.000 Ton/Tahun - Septiani, Tika Nur, Emi Erawati, S.T., M.Eng, r. Nur Hidayati, Ph.D (2016)
Population growth and development in Indonesia in all sectors led to soaring fuel requirements and availability is dwindling. Biodiesel is a fuel of vegetable oils that have properties resembling a diesel or diesel oil with a purity of 98%. Biodiesel is designed with a capacity of 140,000 tonnes/year using raw materials palm oil, methanol and catalyst NaOH. Operating at a temperature of 60°C and a pressure of 1 atmosphere, the mole ratio CPO : methanol of 1: 6, the result of conversion of 98% and the reaction is exothermic. The reaction takes place in the reactor RATB the transesterification process and the liquid-liquid phase, the reactor is equipped with a cooling coil. The land area required for 8065 m2 and total workforce of 155 people. The raw material that is needed is the CPO as much as 17.958.92 kg/hr, methanol amounted to 3.999.22 kg/h, NaOH amounted to 179.59 kg/h and HCl at 160.42 kg/hour. Utility requirements include water from the River Bontang as much as 15.358 kg/h, diesel fuel amounted to 579,63 L/h, the compressed air is 150 m3/h and 675 kWh of electricity needs. The factory will build in Bontang, East Kalimantan. From the results of economic analysis, obtained a fixed capital of Rp. 591.581.941.452. Total production costs per year amounting to Rp. 979.099.726.094. Profit before tax of Rp. 124.410.107.077 per year, profit after tax of Rp. 93.307.580.307 per year. Shows the results of an economic evaluation, that the Percent ROI before tax 21%, after tax 15,8%, the POT before tax of 3,22 years and 3,88 years after tax. BEP SDP 58,12% and amounted to 28,24% and 26,96% DCF. The results of the evaluation expressed Biodiesel from palm oil and methanol with a capacity of 140,000 tonnes/year is quite feasible founded.